2013
DOI: 10.1371/journal.pone.0056162
|View full text |Cite
|
Sign up to set email alerts
|

PBOV1 Is a Human De Novo Gene with Tumor-Specific Expression That Is Associated with a Positive Clinical Outcome of Cancer

Abstract: PBOV1 is a known human protein-coding gene with an uncharacterized function. We have previously found that PBOV1 lacks orthologs in non-primate genomes and is expressed in a wide range of tumor types. Here we report that PBOV1 protein-coding sequence is human-specific and has originated de novo in the primate evolution through a series of frame-shift and stop codon mutations. We profiled PBOV1 expression in multiple cancer and normal tissue samples and found that it was expressed in 19 out of 34 tumors of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 48 publications
2
57
0
Order By: Relevance
“…Wu et al (2011) identified 60 de novo genes in human [22]. Moreover, de novo genes could play essential roles during the evolution of organisms [44,45]. In this study, we also identified five de novo originated OGs in the silkworm ( Supplementary Table S6).…”
Section: Emergence Of the Silkworm Ogsmentioning
confidence: 76%
“…Wu et al (2011) identified 60 de novo genes in human [22]. Moreover, de novo genes could play essential roles during the evolution of organisms [44,45]. In this study, we also identified five de novo originated OGs in the silkworm ( Supplementary Table S6).…”
Section: Emergence Of the Silkworm Ogsmentioning
confidence: 76%
“…Meanwhile, it was found that new genes could also repress tumorigenesis. For instance, prostate and breast cancer overexpressed gene 1 ( PBOV1 ) evolved as a human specific de novo gene, whose expression is associated positively with the survival possibility of patients [30]. …”
Section: New Genes Appear To Promote Tumorigenesis While Evolving Newmentioning
confidence: 99%
“…For example, high expression of PBOV1 correlated positively with relapse-free survival outcomes in breast cancer and glioma in a study based on clinically annotated public microarray data. 15 These results suggested possible "immunoediting" of PBOV1-expressing tumor cells, whereby PBOV1 serves as a tumor antigen facilitating immune attack and elimination of tumor cells based on the presence of PBOV1. A more recent study demonstrated that high levels of PBOV1 mRNA and protein levels in ovarian cancer correlate positively with longer survival and negatively with ascending histological grade, 16 also consistent with a possible immune-stimulatory role for PBOV1 in this setting.…”
Section: Introductionmentioning
confidence: 87%
“…Proteins were extracted using previously described methods. 20 The PBOV1 antibody used in this study was validated as previously described 12 and recognizes epitope B of the PBOV1 protein (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Beta actin (1:15,000, Sigma-Aldrich, St. Louis, MO) was used as a control for data normalization.…”
Section: Optimization Of Western Blot Antibodies and Methodsmentioning
confidence: 99%
See 1 more Smart Citation